Carbon Nanotubes (IntechOpen, 2023)
Carbon Nanotubes are among the strongest, toughest, and most stiff materials found on earth. Moreover, they have remarkable electrical and thermal properties, which make them suitable for many applications including nanocomposites, electronics, and chemical detection devices. This book is the effort of many scientists and researchers all over the world to bring an anthology of recent developments in the field of nanotechnology and more specifically CNTs. In this book you will find: - Recent developments in the growth of CNTs- Methods to modify the surfaces of CNTs and decorate their surfaces for specific applications- Applications of CNTs in biocomposites such as in orthopedic bone cement- Application of CNTs as chemical sensors- CNTs for fuelcells- Health related issues when using CNTs